To find the inverse of a function, switch the variables and solve for y.

Remember that when something says f(x) you can replace it with y.

This is the equation to solve for the inverse

x = 4 / (y + 2)

x(y + 2) = 4

y + 2 = 4 / x

y = 4 / x - 2

Make common denominators

y = 4 / x - 2x / x

y = 4 - 2x / x

y = 2(2 - x) / x

Option (B)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up